2015
DOI: 10.1210/en.2015-1167
|View full text |Cite
|
Sign up to set email alerts
|

Activins A and B Regulate Fate-Determining Gene Expression in Islet Cell Lines and Islet Cells From Male Mice

Abstract: TGFβ superfamily ligands, receptors, and second messengers, including activins A and B, have been identified in pancreatic islets and proposed to have important roles regulating development, proliferation, and function. We previously demonstrated that Fstl3 (an antagonist of activin activity) null mice have larger islets with β-cell hyperplasia and improved glucose tolerance and insulin sensitivity in the absence of altered β-cell proliferation. This suggested the hypothesis that increased activin signaling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the current study, GH reduced activin A secretion and promoted MAFB upregulation, and thus supporting the role of GH in GM-Mf reprogramming. In accord with these results, activin A was shown to suppress MAFB expression in a pancreatic islet cell line (68). MAFB stabilization is controlled by GSK3b (48), an inhibitory serine/threonine kinase that is inactivated by phosphorylation at serine-9 (49).…”
Section: Discussionmentioning
confidence: 54%
“…In the current study, GH reduced activin A secretion and promoted MAFB upregulation, and thus supporting the role of GH in GM-Mf reprogramming. In accord with these results, activin A was shown to suppress MAFB expression in a pancreatic islet cell line (68). MAFB stabilization is controlled by GSK3b (48), an inhibitory serine/threonine kinase that is inactivated by phosphorylation at serine-9 (49).…”
Section: Discussionmentioning
confidence: 54%
“…Before purchasing, all cell lines were authenticated by each supplier. INS-1E cells were analyzed using COI Assay by the supplier (Addex Bio) to ensure no interspecies contamination (40,41). In addition, we performed RNA sequencing to confirm the presence of insulin, observed the cells under microscopy to identify changes in morphology and attachment properties, and maintained growth curves to monitor cell doubling time, growth trends, and passage number.…”
Section: Experimental Design Experimental Model and Subject Detailsmentioning
confidence: 99%
“…However, other, yet similar, experiments with pancreatic explants showed that activin A or activin B (activin-b B dimer) did not affect pancreatic cell differentiation; instead, activin A caused a transdifferentiation of the embryonic pancreatic tissue to intestinal tissue (van Eyll et al 2004). Independent transdifferentiation and signaling experiments confirmed that activin A or activin B suppress exocrine a-cell differentiation and promote endocrine b-cell differentiation, enabling insulin secretion (Andrzejewski et al 2015). The activins repress the expression of a-cell transcription factors and induce b-cell transcription factor expression, and their actions explain the phenotype of mice with a deletion of the Fstl3 gene, encoding follistatin-like 3, which show hyperplasia of their b-islets (Andrzejewski et al 2015).…”
Section: Pancreatic Organogenesismentioning
confidence: 69%
“…Independent transdifferentiation and signaling experiments confirmed that activin A or activin B suppress exocrine a-cell differentiation and promote endocrine b-cell differentiation, enabling insulin secretion (Andrzejewski et al 2015). The activins repress the expression of a-cell transcription factors and induce b-cell transcription factor expression, and their actions explain the phenotype of mice with a deletion of the Fstl3 gene, encoding follistatin-like 3, which show hyperplasia of their b-islets (Andrzejewski et al 2015). Despite these observations, normal pancreatic tissue expresses activin-b A and activin-b B in the epithelium, and follistatin and activin receptors in the mesenchyme (Ritvos et al 1995;Maldonado et al 2000).…”
Section: Pancreatic Organogenesismentioning
confidence: 81%